2006
DOI: 10.1161/01.res.0000238377.08219.0c
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Endothelium-Derived Hyperpolarizing Factor-Mediated Dilations and Increased Blood Pressure in Mice Deficient of the Intermediate-Conductance Ca 2+ -Activated K + Channel

Abstract: Abstract-The endothelium plays a key role in the control of vascular tone and alteration in endothelial cell function contributes to several cardiovascular disease states. Endothelium-dependent dilation is mediated by NO, prostacyclin, and an endothelium-derived hyperpolarizing factor (EDHF). EDHF signaling is thought to be initiated by activation of endothelial Ca 2ϩ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
232
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(247 citation statements)
references
References 47 publications
11
232
4
Order By: Relevance
“…Therefore, it is most likely that spontaneous Ca 2+ events in our present study can cause STOCs originating in endothelial cells and contribute to the activation of SK Ca or IK Ca , resulting in hyperpolarization to regulate vascular tone. Certainly, consistent with this suggestion mice deficit in either SK Ca or IK Ca have a raised blood pressure [33,34].…”
Section: Discussionmentioning
confidence: 62%
“…Therefore, it is most likely that spontaneous Ca 2+ events in our present study can cause STOCs originating in endothelial cells and contribute to the activation of SK Ca or IK Ca , resulting in hyperpolarization to regulate vascular tone. Certainly, consistent with this suggestion mice deficit in either SK Ca or IK Ca have a raised blood pressure [33,34].…”
Section: Discussionmentioning
confidence: 62%
“…Ca 2+ -activated K channels including small-conductance, intermediate-conductance and bigconductance have been shown to be expressed in endothelial cells [1][2][3][4][5]. Although Ca 2+ -activated small conductance and intermediate-conductance K channels are mainly responsible for determining the membrane potential under basal conditions [3], BK channels may also be involved in regulating the membrane potential of endothelial cells because BK channels have a high channel conductance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the impairment of K Ca 2.3 and K Ca 3.1 affects the endothelium‐dependent control of vascular contractility, which results in a predisposition to vascular diseases (Grgic et al ., 2009). An increase in blood pressure has been reported in K Ca 3.1 knockout mice (Si et al ., 2006), and we have previously suggested that K Ca 3.1 downregulation is a cause of endothelial dysfunction in Fabry disease (Park et al ., 2011). In addition, we reported that superoxide generated from ECs downregulates K Ca 3.1, resulting in endothelial dysfunction in preeclampsia (Choi et al ., 2013a).…”
Section: Introductionmentioning
confidence: 90%